Women and Matrimony: A Study of Mona Lisa Smile - Pei-Yu Chao; Ya-huei Wang (Journal of Language and Literature, 2021)
This study intended to use the film Mona Lisa Smile (1993) as an example to examine how women in the traditional generation of 1950 were gender stereotyped and used to trade themselves off through marriage in consideration of a cost-and-benefit analysis. However, as the change of women’s gender consciousness from the conservative to the feminist in the USA of 1950, women began to realize their potential and subjectivity, hence questing for liberal spirit and autonomy to choose their career and husbands based on love. The researchers used the qualitative method, with both the primary and secondary data, to facilitate a latent-content analysis. After conducting a content analysis of the film and the script of Mona Lisa Smile, the researchers took notes regarding gender stereotyping and conventional gender norms in social interactions and conducted a literature review of Becker’s side bet theory and Homan’s social exchange theory to investigate how women in America in the 1950s were disciplined to meet the expectation of social norms to fit the notion of conventional matrimony, and how people, both men and women, while choosing their mates, seek the maximum interest and minimum cost. The film Mona Lisa Smile lets readers have a chance to see the transformation of a marital relationship from the old days to modern ones. With raised gender consciousness, women may now subject their choices to their own will and, hence, apply a different definition to the word “marriage.”